Exploring motivations driving student entrepreneurship: A case study of Innobiz DUT centre for entrepreneurship and innovation - Chitamba, Anos; Mugano, Gift; Mbona, Sizwe; Chitamba, Norman (Edelweiss Applied Science and Technology, 2025)
Entrepreneurship is increasingly recognized as a significant catalyst for economic growth, innovation, and job creation, especially in developing countries such as South Africa, where youth unemployment poses a substantial challenge. Higher education institutions play a crucial role in nurturing entrepreneurial aspirations among students by equipping them with the skills necessary for self-sufficiency and societal contribution. The Durban University of Technology’s (DUT) Innobiz Centre for Entrepreneurship and Innovation exemplifies this commitment by promoting entrepreneurial mindsets through experiential learning, mentorship, and resource support. This study investigates the motivations influencing student entrepreneurship within the framework of the Innobiz Centre for Entrepreneurship and Innovation, utilizing a quantitative research design and survey methodology to evaluate factors such as personal fulfillment, societal impact, and career aspirations. Data were collected from 76 students involved in entrepreneurial initiatives at the center, with responses analyzed using descriptive and inferential statistics. Findings indicate key motivators, including opportunities for innovation (mean = 2.89), creative autonomy (mean = 2.88), and financial independence (mean = 2.86). Although students recognize entrepreneurship as a pathway to achieving career objectives and addressing socio-economic challenges, intrinsic motivations, such as self-expression and innovation, are shown to surpass extrinsic influences like role models. Additionally, the results highlight a moderate emphasis on societal contributions and community impact, reflecting the growing importance of social entrepreneurship. Nevertheless, challenges such as limited funding and psychological barriers remain. The study’s findings offer actionable insights for enhancing entrepreneurial ecosystems within higher education, underscoring the need for targeted interventions to address motivational drivers and institutional obstacles. Institutions such as DUT can better prepare students to navigate economic challenges and contribute positively to society by strengthening support structures and fostering innovation.